2016
DOI: 10.1289/ehp.1409450
|View full text |Cite
|
Sign up to set email alerts
|

A Workflow to Investigate Exposure and Pharmacokinetic Influences on High-Throughput in Vitro Chemical Screening Based on Adverse Outcome Pathways

Abstract: BackgroundAdverse outcome pathways (AOPs) link adverse effects in individuals or populations to a molecular initiating event (MIE) that can be quantified using in vitro methods. Practical application of AOPs in chemical-specific risk assessment requires incorporation of knowledge on exposure, along with absorption, distribution, metabolism, and excretion (ADME) properties of chemicals.ObjectivesWe developed a conceptual workflow to examine exposure and ADME properties in relation to an MIE. The utility of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…The previous study 17 also identified 22 possible false negatives out of chemicals considered inactive in the same assay, based on their structural similarities to active chemicals. Since the analysis here required in vitro dose–response data, which is lacking for most inactive chemicals, only five of the 22 false negatives were carried over to the current study.…”
Section: Methodsmentioning
confidence: 99%
“…The previous study 17 also identified 22 possible false negatives out of chemicals considered inactive in the same assay, based on their structural similarities to active chemicals. Since the analysis here required in vitro dose–response data, which is lacking for most inactive chemicals, only five of the 22 false negatives were carried over to the current study.…”
Section: Methodsmentioning
confidence: 99%
“…Vinken et al , for example, developed AOPs describing the stepwise mechanistic association between the drug-implicated MIE of inhibition of the bile salt export pump and the organismal development cholestatic liver injury [108]. When combined with exposure and ADME assessments, the AOP framework has recently been demonstrated by Philips et al to identify drug metabolites and parent compounds that in fact engage in an MIE and therefore avoid unnecessary costs of comprehensive biological assessment [109]. Figure 3 outlines how the AOP concept might contribute to a preclinical drug metabolism assessment workflow, wherein predicted or experimentally established exogenous metabolites are screened for adverse outcomes according to the current knowledgebase.…”
Section: Computational Tools For Studies Of Drug Metabolismmentioning
confidence: 99%
“…In this tier, qualitative evaluation of ADME potential could aid in the identification of false positives, which are in vitro active chemicals that cannot reach the molecular target in vivo due to certain ADME characteristics (Phillips et al, 2015). For example, some chemicals (e.g., anthralin) can be sequestered in skin tissues; therefore, they are unlikely to enter the systemic circulation-and thus molecular targets in internal organs-when exposed via a dermal route.…”
Section: Adverse Outcome Pathways-evolution Of the Conceptmentioning
confidence: 99%
“…For example, some chemicals (e.g., anthralin) can be sequestered in skin tissues; therefore, they are unlikely to enter the systemic circulation-and thus molecular targets in internal organs-when exposed via a dermal route. In addition, chemical structures or molecular descriptors could potentially be used to detect possible false negatives that are either inactive parents of active metabolites or in vivo active chemicals not detected in vitro (Phillips et al, 2015).…”
Section: Adverse Outcome Pathways-evolution Of the Conceptmentioning
confidence: 99%